Optimization and physicochemical characterization of polymeric nanoparticles containing tinidazole - Ho, Hoang Nhan; Le, Hoang Hao; Ho, Thi Thu Hue; Phan, Thi Thao Ngoc (Tạp chí Y Dược Huế, 2023)
Background: Periodontitis is a chronic bacterial infection destroying tooth-supporting tissues. Like metronidazole, tinidazole (TNZ) is also effective in treating periodontitis. The preparation of polymeric nanoparticles containing TNZ helps to improve the solubility and increase the bioavailability of the drug. Objectives: This study aimed to formulate and optimize TNZ nanoparticles and evaluate their physicochemical properties. Materials and methods: TNZ, Eudragit RSPO polymer as a carrier were used in this study. TNZ- loaded nanoparticles (TNZ NPs) were prepared by the solvent evaporation - emulsion method. The influence of the factors in the formula and the preparation process of TNZ NPs was investigated and optimized using MODDE 13.0 software. The physicochemical properties of NPs were evaluated by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and in vitro drug release. Result: The optimal TNZ NPs were spherical in shape, mostly amorphous, with particle size of 179.60 ± 2.20 nm, polydispersity index of 0.149 ± 0.024, and encapsulation efficiency of 47.49 ± 0.02%. TNZ NPs showed prolonged drug release in phosphate buffer pH 6.8 for up to 24 hours. Conclusions: The optimal TNZ NPs would be a promising drug delivery system for periodontitis treatment.